Anatomic study of the bifurcation of the obturator nerve: application to more precise surgical/procedural localization - Iwanaga, Joe; Ishak, Basem; Yilmaz, Emre; von Glinski, Alex; Gielecki, Jerzy; Dumont, Aaron S.; Tubbs, R. Shane (World neurosurgery, 2020)
Background - This anatomic study aimed to more precisely locate the bifurcation of the obturator nerve in relationship to the obturator foramen. Such information might improve outcomes in neurotization or other procedures necessitating exposure of the obturator nerve and could increase success rates for obturator nerve blockade. - Methods - Fourteen sides from fresh-frozen cadaveric specimens were used in this study. Dissection of the obturator nerve was performed, and its bifurcation into anterior and posterior branches was documented and classified. Measurements of these branches were also performed. Bifurcations of the obturator nerve were classified as type I when proximal to the obturator foramen, type II when inside the obturator foramen, and type III when distal to the obturator foramen. - Results - Type I, type II, and type III obturator nerve bifurcations were observed in 14.3%, 64.3%, and 21.4% of sides, respectively. In type I nerves, the mean distance from the bifurcation of the obturator nerve to the obturator foramen was 15.8 mm, and in type II nerves the mean was 14.0 mm. The mean diameter of the main trunk, anterior branch, and posterior branch was 3.74 mm, 2.64 mm, and 2.28 mm, respectively. - Conclusions - Bifurcation of the obturator nerve can occur proximally, distally, or inside the obturator foramen. Therefore using imaging modalities such as ultrasound is strongly recommended for identifying the main trunk or anterior and posterior branches of the obturator nerve before surgery or other procedures aimed at this nerve due to such anatomic variations.
Gesehen am 18.09.2020